Spanish-Arabic and Arabic-Spanish Translation: an Outlook and an Intercultural Perspective - El Bohdidi, Miloud (Íkala, Revista de Lenguaje y Cultura, 2017)
Building bridges of understanding is a sine qua non condition to strengthen fraternity between countries in the Mediterranean area, and translation practice is a privileged way for cultural exchange in this geographic zone. We aim to expose the role of translation as an instrument for intercultural development between Spain and Morocco. Both countries’ geographic location on the Mediterranean is a factor leveraging common interests. In this geographic, political and social context we estimate Spanish-Arabic and Arabic-Spanish translation turns to be critical both for intercultural Spanish-Moroccan communication and to create mutual positive perceptions and removing topics common in communication. Arabic learning in Spain and Spanish learning in Morocco is, therefore, a critical challenge to develop intercultural competence